FAKTOR PENENTU KEPUTUSAN PEMBELIAN PADA PRODUK TAHU DI PERUSAHAAN XYZ - Afiff, Fatimah Zahra; Andriana, Iyan; Hafizh, Muhammad Rafi (Inaque : Journal of Industrial and Quality Engineering, 2025)
The company does not know what factors influence purchasing decisions. There are several customer values that will influence purchasing decisions, such as emotional value, social value, quality value and functional value. In order to identify the factors that influence customers to buy products from the company, the questionnaire survey method, and multiple linear regression are used to process the results. The questionnaire is based on the variable design of the questionnaire, with emotional value, social value, quality value, and functional value as independent variables, and purchase decision-making as the dependent variable. Based on the results of the calculation, it is concluded that the effect of emotional value on purchasing decisions is not significant, which is 1.911. The effect of social value on purchasing decisions is not significant, which is 0.526. The effect of quality value on purchasing decisions is not significant, which is 1.386. The effect of functional value on purchasing decisions is not significant 4.954 significant effect. The results of the frequency of answers to each functional value indicator which has the greatest influence on purchasing decisions, namely product inventory and environmental cleanliness by 17.36%.